Motivation to study medicine of medical students at Faculty of Medicine, Chulalongkorn University. - Lawanont, N.; Pityaratstian, N.; Phativarakorn, P. (Chulalongkorn Medical Journal, 2023)
Background : Initial inspiration to become a doctor is unique for each person. Some of our motivations get stuck by outside influences such as parental expectations and living up to someone else’s dreams. The authors are interested in studying the motivations and associated factors of medical students. Objective : To study motivations and associated factors of medical students at the Faculty of Medicine, Chulalongkorn University. Methods : Samples were 870 medical students from year 1 to 6 of the Faculty of Medicine, Chulalongkorn University in academic year 2015. The instruments were a set of questionnaires that consisted of 3 parts: 1) demographic questionnaires; 2) Depression Anxiety Stress Scales questionnaires (DASS-21); 3) The Strength of Motivation for Medical School-Revised questionnaires (SMMS-R). Results : Most medical students had moderate motivation of willingness to sacrifice, moderate motivation of readiness to start, and high motivation of persistence. The significantly associated factors with overall motivations and motivation subscales were: gender, age, year(s) of study, admission program, GPAX, residential style, monthly income, exercise, average time spent on daily reading, leisure time, participation in extracurricular activities, desire to become a doctor, reason to study medicine and mental health status. The predictive factors of overall motivations were year(s) of study (2nd year), average time spent on daily reading, and participation in extracurricular activities. Conclusion : To study medicine, many factors are related to motivation in medical students. Findings from this research can be useful in adapting the medical education processes to bring out the best from them.